Xanthoneuria, a new genus of stonefly (Plecoptera: Perlidae) from Japan - Uchida, Shigekazu (Illiesia, 2011)
Xanthoneuria is proposed as a new genus of acroneurine stonefly with Acroneuria fulva (Klapálek) as type species. Xanthoneuria bolivari (Klapálek),new combination, X. jouklii (Klapálek), new combination, and X. unimaculata (Zhiltzova) are also transferred to the new genus, and a key is presented to assist in distinguishing Japanese members of the genus.
Keywords: entomology; Perlidae; Plecoptera; Xanthoneuria; entomologija; new genus; Japan; vrbnice; Japonska